Petrography and provenance of basement clasts in CIROS-1 core, McMurdo Sound, Antarctica - SANDRONI, S.; TALARICO, F. M. (2004)
Petrographical, mineral chemistry and distribution data on pebble- to boulder-size clasts in the Early Miocene-Late Eocene sedimentary succession recovered at CIROS-1 drillsite (McMurdo Sound) are described here. Clasts are dominated by granitoids and dolerites, with minor occurrences of sedimentary, volcanic and metamorphic rocks. Granitoid clasts are mainly represented by deformed or undeformed biotite and biotite-hornblende monzogranites, with minor occurrences of leucogranites, porphyries and tonalites. Metamorphic rocks consist of orthogneisses and metasediments, including both medium- to high-grade and low-grade varieties. Clast distribution suggests three major episodes of erosion, which punctuate the uplift and unroofing history of the Transantarctic Mountains in Victoria Land. Erosion of cover rocks (Beacon and Ferrar Supergroups) dominates during the first and second phases (c. 702 to c. 200 mbsf), while the third erosional phase is mainly connected to the deeper unroofing of basement rocks (Granite Harbour Intrusive Complex and Koettlitz. Group; above c. 200 mbsf). The source area is identified with the Transantarctic Mountains sector adjacent to New Harbour (Dry Valleys and Royal Society blocks). All the phases are consistent with a clast provenance mainly within the Dry Valleys Block, the Royal Society Block being subordinately involved only within the earliest and latest sedimentation of the cored succession (c. 702 to c. 326 mbsf and above c. 200 mbsf).